2015
DOI: 10.3390/rs70911163
|View full text |Cite
|
Sign up to set email alerts
|

NDVI-Based Analysis on the Influence of Climate Change and Human Activities on Vegetation Restoration in the Shaanxi-Gansu-Ningxia Region, Central China

Abstract: Abstract:In recent decades, climate change has affected vegetation growth in terrestrial ecosystems. We investigated spatial and temporal patterns of vegetation cover on the Loess Plateau's Shaanxi-Gansu-Ningxia region in central China using MODIS-NDVI data for 2000-2014. We examined the roles of regional climate change and human activities in vegetation restoration, particularly from 1999 when conversion of sloping farmland to forestland or grassland began under the national Grain-for-Green program. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(69 citation statements)
references
References 51 publications
(59 reference statements)
2
56
0
2
Order By: Relevance
“…On the reasons for the vegetation restoration in the Loess Plateau in the last decade, many studies also argued that it was the comprehensive effects of climate change and human activities. S. S. Li, Yang, Liu, Liu, and Shi () argued the vegetation restoration in Shaanxi‐Gansu‐Ningxia region was because greater precipitation occurred at a later stage of ecological engineering, and Y. R. Li et al () argued that the vegetation restoration in Mu Us Sandy Land was the joint effects of climate change, ecological restoration, and agricultural activities. This paper analysed the driving forces regionally.…”
Section: Discussionmentioning
confidence: 99%
“…On the reasons for the vegetation restoration in the Loess Plateau in the last decade, many studies also argued that it was the comprehensive effects of climate change and human activities. S. S. Li, Yang, Liu, Liu, and Shi () argued the vegetation restoration in Shaanxi‐Gansu‐Ningxia region was because greater precipitation occurred at a later stage of ecological engineering, and Y. R. Li et al () argued that the vegetation restoration in Mu Us Sandy Land was the joint effects of climate change, ecological restoration, and agricultural activities. This paper analysed the driving forces regionally.…”
Section: Discussionmentioning
confidence: 99%
“…NDVI fluctuates due to favourable or unfavourable weather and environmental conditions (Dąbrowska-Zielińska, Ciołkosz, Malińska, & Bartold, 2011; Dąbrowska-Zielińska, Kogan, Ciolkosz, Gruszczynska, & Kowalik, 2002;Kogan, 1997). NDVI has been widely used to estimate the influence of climatic conditions on vegetation activities globally (Ichii, Kawabata, & Yamaguchi, 2002) and in different regions (Ivanovs & Lupikis, 2018;Li, Yang, Liu, Liu, & Shi, 2015;Sağır, Le Coz, Kurtuluş, & Razack, 2017;Usman, Yelwa, Gulumbe, & Danbaba, 2013). NDVI has been widely used to estimate the influence of climatic conditions on vegetation activities globally (Ichii, Kawabata, & Yamaguchi, 2002) and in different regions (Ivanovs & Lupikis, 2018;Li, Yang, Liu, Liu, & Shi, 2015;Sağır, Le Coz, Kurtuluş, & Razack, 2017;Usman, Yelwa, Gulumbe, & Danbaba, 2013).…”
mentioning
confidence: 99%
“…This demonstrated that the land use by urban expansion was controlled effectively by the steppe protection programs and conservation policies in place in China between 2001-2010 [40,62,64]. However, there was still some steppe degradation caused by building activity [49,63], such as in the Liao River basin [63], as shown in Figures 3 and 5, which indicates that the steppe protection programs and conservation policies should be continued. We found that the effect of deforestation and farming dropped off over the course of the decade, which revealed that the Grain for Green Project has performed well [16,64].…”
Section: Driving Forces Of Dynamics Of Steppe Sustainabilitymentioning
confidence: 99%
“…The most popular methods used recently are to monitor Steppe dynamics with NDVI [17,[41][42][43][44][45][46][47][48][49] and to monitor dynamics of ecosystem productivity with NPP [33,[50][51][52][53][54][55]. In addition, the most important indicator of steppe sustainability is ecosystem productivity; therefore, steppe dynamics has been monitored with NDVI, and the dynamics of steppe sustainability were assessed with NPP in this study.…”
Section: Assessing Methods On Dynamics Of Steppe Sustainabilitymentioning
confidence: 99%